2022
DOI: 10.29309/tpmj/2022.29.08.6837
|View full text |Cite
|
Sign up to set email alerts
|

Medical disorders in pregnancy a tertiary care hospital experience.

Abstract: Objective: To determine the exact magnitude of the problem in our setup which will help to develop consensus guidelines with the contribution from various specialists especially obstetric medical specialist. Study Design: Prospective Observational study. Setting: It was conducted on 2448 patients who were ill due to various medical conditions during pregnancy and admitted to PNS Shifa and CMH Kharian. Period: 1st Jun 2019 till 31st May 2021. Material & Methods: Data was collected from the patients in the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…11 Similarly, another study reported that Chronic hypertension occurs in approximately 1 to 5% of pregnancies, gestational hypertension in around 5 to 6%, and pre-eclampsia in nearly 3 to 6% of pregnancies based on population data. 16 10 Similarly, another study reported a similar result of 10.84% GDM occurrence. 4 The present study identied renal and urinary tract infections as the fourth major group of medical disorders aecting 175 (9.67%) patients.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…11 Similarly, another study reported that Chronic hypertension occurs in approximately 1 to 5% of pregnancies, gestational hypertension in around 5 to 6%, and pre-eclampsia in nearly 3 to 6% of pregnancies based on population data. 16 10 Similarly, another study reported a similar result of 10.84% GDM occurrence. 4 The present study identied renal and urinary tract infections as the fourth major group of medical disorders aecting 175 (9.67%) patients.…”
Section: Resultsmentioning
confidence: 57%
“…showed a low incidence of 5.22%. 10,14,15 In a study conducted in Nigeria, hypertensive disorders ranked second, after malaria, with a frequency of 29.2%. 11 Similarly, another study reported that Chronic hypertension occurs in approximately 1 to 5% of pregnancies, gestational hypertension in around 5 to 6%, and pre-eclampsia in nearly 3 to 6% of pregnancies based on population data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation